Hennady Liashenko: the perspectives of life and creative work - Rzhevska, Mayya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of research. Hennady Liashenko is one of the leading Ukrainian composers of the last third of the XXth – beginning of the XXIst century, a well-known musicologist, pedagogue and a musical and social activist who has substantially contributed to the treasure house of music culture. His legacy that blends seamlessly into the context of global academic music at the same time by no doubt possesses the traits of affiliation with the national culture. That is exposed by both choice of the topics of the compositions and involving texts of the Ukrainian writers into their figurativeness and in music language together with the system of musical and dramaturgical techniques. The goal of the article is to define the main stages of the composer's life journey in their direct relation to his creative work. The research methods are biographical (to recreate the mechanisms and events that determined the composer's personality formation), as well as the suite of methods of musicological research. Conclusion. The composer's life journey is connected to the different regions of Ukraine which has determined his understanding of the homeland as an integrity and the completeness of perception of the national culture in its different aspects. An important role in the composer's formation was played by his studies in Lviv Conservatory, an educational institution with European academic traditions and openness to the new trends in art. The main genre fields of H. Liashenko creative work are symphonic, chamber instrumental and choir music. The traits of his style are determined by deep philosophical aspect, succession in terms of mainstream lines of development of the European music culture, affiliation with the Ukrainian cultural tradition, connection with the literature. The composer's style is also characterized by the national determinancy of artistic language, acute conflicts, search of special for every creation dramaturgical solutions, synthesis of the rational and the emotional, applying different composition techniques, polyphony of texture. Practical significance. The results of the research confirm the unique character of the composer's creative personality, the artistic and sense bearing depth and absolute value of his creative work.